The Role of the Qanun in the Development of Mangrove Forest Ecotourism in Kuala Langsa, Aceh - Sahudra, Tengku Muhammad; Desfandi, Mirza; Nisa, Jakiatin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
Kuala Langsa has a large tourism potential to be developed, however, the lack of understanding of ecotourism regulations by stakeholders can hamper the development of the area into a mangrove ecotourism area that is following the principles of development. This paper discusses the role of the qanun in the development of mangrove ecotourism in Kuala Langsa, Aceh. The type of legal research used in this paper is a normative research method, then analyzed using a qualitative approach, with different analysis methods. The results of this paper indicate that in optimizing the development of coastal areas it is necessary to strengthen and explore Qanun and policies that have been regulated by the government. The development and management of tourism areas have been regulated in Aceh Qanun No. 8 of 2013 concerning Tourism. However, the regulation has not been running optimally due to the low understanding of the community regarding the tourism Qanun even though it is intended to provide legal legality for each stakeholder to be able to increase their capacity.